2018
DOI: 10.1017/s026646231800212x
|View full text |Cite
|
Sign up to set email alerts
|

PP50 Microcosting With Time-Driven Activity-Based Costing Applied On Brazilian HTA System: ECMO Case Study

Abstract: Introduction:Extracorporeal circulatory membrane oxygenation (ECMO) is a technology that allows recovery of adults in cardiorespiratory failure with encouraging results, but is not available in the Brazilian universal public health system (SUS) due to high implementation costs. Time-driven activity based costing (TDABC) is applied to measure processes in an economic perspective by identifying opportunities to make processes more efficient through the reduction of resources used in each activity. The literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a Dutch study, the mean cost of ECMO patients was (Euros) 106.263 and 52% of these costs arose from nursing care and only 11% from the ECMO surgery and materials [28]. In Brazil, a short cohort study in 2018 demonstrated that ECMO materials and surgery represented 11% of the cost per patient for surviving patients, 30% for those who died [29]. These previous experiences highlight the importance of taking the right decision on using the technology, at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…In a Dutch study, the mean cost of ECMO patients was (Euros) 106.263 and 52% of these costs arose from nursing care and only 11% from the ECMO surgery and materials [28]. In Brazil, a short cohort study in 2018 demonstrated that ECMO materials and surgery represented 11% of the cost per patient for surviving patients, 30% for those who died [29]. These previous experiences highlight the importance of taking the right decision on using the technology, at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…29 In Brazil, a short cohort study in 2018 demonstrated that ECMO materials and surgery represented 11% of the cost per patient for surviving patients, 30% for those who died. 30 These previous experiences highlight the importance of making the right decision on using the technology, at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…In a Dutch study, the average cost of ECMO patients was (Euros) 106.263% and 52% of these costs arose from nursing care and only 11% from the ECMO surgery and materials 29 . In Brazil, a short cohort study in 2018 demonstrated that ECMO materials and surgery represented 11% of the cost per patient for surviving patients, 30% for those who died 30 . These previous experiences highlight the importance of making the right decision on using the technology, at the right time.…”
Section: Discussionmentioning
confidence: 99%